PROBLEMS OF ENGLISH LEXICOGRAPHY (Yangi O'zbekiston taraqqiyotida tadqiqotlarni o'rni va rivojlanish omillari, 2024)
This theme explores the various challenges facing lexicographers in the field of English lexicography, which involves thecompilation and updating of dictionaries